Institutionalisation of Social Enterprise in Romania: Historical Milestones and SE Models Development - Lambru, Mihaela; Petrescu, Claudia (Social Enterprise in Central and Eastern Europe, 2021)
This chapter presents the evolution and current situation of social enterprise (SE) in Romania. It analyses the historical background that has influenced the inception and development of social enterprises in the country. The chapter presents the main stages that can be distinguished in the development of social enterprises in Romania, highlighting for each stage important legislative benchmarks. It provides a presentation of the different SE models that people have identified. The chapter analyses current trends and challenges in the Romanian SE field. In Romania, the revival of the associative sector and the development of social-economy organisations, including social enterprises, were made possible by the systemic political changes that occurred after 1989. The development of a policy environment fostering the growth of social enterprises in the country has been strongly influenced by the structural changes that have taken place since the 1990s in two main strategic areas: social-policy reform and public-administration reform.